2021
DOI: 10.3389/fgene.2021.700371
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 15 Is Associated With Alzheimer’s Disease Risk

Abstract: BackgroundPrevious observational studies have suggested that associations exist between growth differentiation factor 15 (GDF-15) and neurodegenerative diseases. We aimed to investigate the causal relationships between GDF-15 and Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS).MethodsUsing summary-level datasets from genome-wide association studies of European ancestry, we performed a two-sample Mendelian randomization (MR) study. Genetic variants significantly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Previous MR studies on Alzheimer's disease 10,12,[25][26][27][28][29][30][31][32][33] suggest potential causal associations with BIN1, CCL27, C3, CD33, CD4 T cells, GDF-15 and SVEP1, whereas MR studies on Parkinson's disease suggest a potential causal association with GPNMB, IL-6 and MIP1b. Compared with these studies, we used a stricter P value cutoff with multiple testing correction and were able to replicate associations between BIN1, CD33 and Alzheimer's disease and those between GPNMB and Parkinson's disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous MR studies on Alzheimer's disease 10,12,[25][26][27][28][29][30][31][32][33] suggest potential causal associations with BIN1, CCL27, C3, CD33, CD4 T cells, GDF-15 and SVEP1, whereas MR studies on Parkinson's disease suggest a potential causal association with GPNMB, IL-6 and MIP1b. Compared with these studies, we used a stricter P value cutoff with multiple testing correction and were able to replicate associations between BIN1, CD33 and Alzheimer's disease and those between GPNMB and Parkinson's disease.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, this is the most comprehensive MR and triangulation study to date on immune system-and BBB-related biomarkers as risk factors of dementia-causing diseases. Our MR focused on 1,827 biomarkers whereas earlier MR analyses included fewer than 200 biomarkers specific to these systems 10,12,[25][26][27][28][29][30][31][32][33] . We obtained the strongest causal evidence for autoimmunity-and inflammation-related AZGP1 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in humans have found an association between high circulating levels of GDF15 and the risk of dementia, cerebrovascular disease, cognitive impairment, and brain atrophy, which are clinical features of many neurodegenerative diseases ( Fuchs et al, 2013 ; Chai et al, 2016 ; Jiang et al, 2016 ; Nasrabady et al, 2018 ). In particular, some studies suggested that high circulating levels of GDF15 are associated with the risk of developing AD, as well as other neurodegenerative diseases, and considered this protein as a promising diagnostic biomarker and therapeutic target of several neurodegenerative diseases ( Chai et al, 2016 ; Wu et al, 2021 ; Xue et al, 2022 ). On the other hand, other studies have found no difference in the circulating level of GDF15 in AD patients compared to age-matched healthy controls ( Conte et al, 2021 ), or showed that exogenous recombinant GDF15 can promote Aβ clearance activity of microglial cultured cells ( Kim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although some suggested that GDF15 is not associated with AD, others demonstrated specific roles for GDF15 in the development of AD [ 20 ]. Elevated GDF15 was associated with a higher risk of AD and lower total brain and hippocampal volumes, greater white matter hyperintensity volume, and poorer cognitive performance [ 21 , 22 ]. Moreover, exogenous recombinant GDF-15 diminished antibody levels in microglial cell culture, and being injected in the brain parenchyma of 5XFAD mice also led to a decrease in Aβ plaques [ 23 ].…”
Section: Introductionmentioning
confidence: 99%